MATERNAL FACTORS ON LABOR WITH CESAREAN SECTION HISTORY - Qonita Hanifah; Linda Dewanti; Ernawati Ernawati (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground : Cesarean section without medical indications can have negativity in developing or developed countries. Cesarean section is a medical intervention in certain circumstance but must be recognized as a major surgical procedure with potential risks to the mother and baby. This research aim to analyze maternal factors in labor with a history of cesarean esction. Method : this research was a cross sectional method with collected 72 medical records in RSUD Dr. M. Soewandhie Surabaya. Result : Maternal age, interpregnancy interval, indication of past Cesarean section, and BMI during pregnancy, did not correlate with method of delivery. Factors which correlated to method of delivery after Cesarean section were prior vaginal delivery (p=0,044) and length of stay (p=0,000). Conclusion : There is a relationship between the factors of vaginal birth history and length of stay with delivery method.